Language, Ideology and Power Relations in Nigerian Television Talk Shows (2015)
Television talk shows (TTSs) are forms of talk-in interactive programmes where hosts and participants employ different discourse strategies, laden with latent ideologies – ideas that reflect their beliefs and interests – and power relations – the controlling of contributions by more powerful participants. Previous studies on Nigerian TTSs described their discourse strategies using conversation analysis, without adequate emphasis on their ideological basis and linguistic features. This study, therefore, examined the ideologies and forms of power relations in Nigerian TTSs in order to elicit their linguistic and paralinguistic cues. The theoretical framework combined van Dijk‟s, Fauconnier and Turner‟s approaches to Critical Discourse Analysis and complemented them with Brown and Levinson‟s Politeness Principle and Poyatos‟ approach to non-verbal communication. The following public-owned stations – Nigerian Television Authority (NTA) and Lagos Television (LTV); and private-owned stations – Silverbird Television (STV) and Africa Independent Television (AIT) were purposively selected for having more talk show content. Eight talk shows: „Today on STV‟ and „Head to Head‟ (STV); „Focus Nigeria‟ and „Kakaaki‟ (AIT); „Daytime Talk‟ and „Morning Desk‟ (LTV); „Good Morning Nigeria‟ and „Reflections‟ (NTA); and three episodes of each, produced between 2012 and 2014, were purposively selected for possessing linguistic categories that accounted for ideologies and power relations. Data were subjected to critical discourse analysis. The ideological underpinnings of the selected Nigerian TTSs vary, as revealed in the accompanying quoted expressions. NTA‟s talk shows employed pro-government and social-democratic ideologies: „„government has insurgency in control‟‟ and “federal government is committed to creating a better Nigeria”. LTV‟s talk shows employed libertarian ideologies aligned to the state party and in opposition to NTA: “federal government is a failure” and “government is the political Boko Haram”. STV‟s talk shows expressed more social-democratic ideologies – “striking unions are insensitive” and “protesters against government are charlatans”; while AITs‟ expressed more liberal ideologies – “federal government deserves media support in the fight against Boko Haram” – both talk shows in favour of federal government. Power relations were evident in domination of turns and topics, guffawing satirical laughter and aggressive portrayal of ideologies in STV shows through shouting and fuming by participants and hosts‟ deployment of face threatening acts. NTA hosts ignored salient points against the station‟s ideologies and interrupted participants‟ turn to avoid revealing mitigating information. However, AIT and LTV talk shows were more cooperative. In the selected talk shows, hosts and participants employed linguistic cues such as relational modality to express commitment to the truth; indirect quotations and presuppositions to expose their non-neutral stance; and „pretentious‟ positive other-presentation and negative self-presentation to express ideologies. The paralinguistic cues observed were eye contacts by hosts and participants to reveal states of disbelief; lack of it to show psychological distance; and low pitch in voice to signal hesitation and disappointment. The selected Nigerian television talk shows are replete with leftist and conservative ideologies expressed by hosts and participants in an atmosphere of dominating and cooperative power relations. The talk shows rely heavily on linguistic and paralinguistic cues that promote their latent ideologies and determine how power relations are negotiated